Recanalization of an atretic intramural left main coronary artery after bypass surgery in a pediatric patient with anomalous aortic origin of the left main coronary artery arising from the right sinus of Valsalva. Issue 4 (5th December 2019) - Orr, William B.; Johnson, Mark C.; Abarbanell, Aaron M.; Sintek, Marc
Abstract: We report a pediatric patient with nonatherosclerotic chronic total occlusion (CTO) of the left main coronary artery (LMCA) leading to complete LMCA atresia which was successfully recanalized via retrograde techniques through a previous internal mammary bypass graft. After the CTO was treated, the artery was found to be anomalous off the right cusp with an intramural coarse and slit‐like orifice. The patient's ischemic symptoms resolved after Percutaneous Coronary Intervention (PCI), and she has continued to do well.